Orality-if anything, Imagination, resistance in dialogue with the discourse of the historical "Other" - Hendricks, Gavin P. (HTS teologiese studies, 2019)
South Africa has a long history of orality deeply embedded in the archival memory of the ‘Other’ or the history of the poor and oppressed. Their untold stories, undocumented histories with displacing identities are how the historical ‘Other’ has been perceived by colonialism and the apartheid regime. The ‘Other’ or primary oral communities in the context of this article can be seen by a name, a face and a particular identity, namely, indigenous people. This article will engage the work of Finnegan on what is ‘Orality – if anything’. The term ‘orality’, as a conceptual tool, can help us to widen our horizons and attention to forms of human creativity and imagination which was neglected or unnoticed by scholars. Orality has forced scholars to ask new questions on what is the meaning of ‘text’ and encouraged and challenge scholars in orality and literacy research with a new analysis of what we thought we already knew. The article engages oral and written research and how it can assist in understanding the discourse of the ‘Other’ and the power relation in reconstructing and re-ordering of their social universe through collective memory, songs, rituals, satire, drama and political protest which at large was perceived by the apartheid era and Western colonisers as savage, uncivilised and barbaric. The oral discourse of the ‘Other’ has become part of the power struggles politically and educationally in South Africa. Orality has further reshaped the Christian discourse in South Africa and Africa as the poor and oppressed find new power in a discourse of metaphysics of presence of the Gospel through preaching and bearing witness of their new encounter spiritually.